Involving elderly research participants in the co-design of a future multi-generational cohort study - Nunn, Jack S. (Res Involv Engagem, 2021)
BACKGROUND: It has been proposed that the existing ASPirin in Reducing Events in the Elderly Extension observational cohort study (ASPREE-XT) would provide a platform for a future multigenerational research study (MGRS). An advert was sent to 14,268 participants (aged 74 years and older, from Australia, and located in both metropolitan and rural locations) to invite them to share views and preferences about being involved in the co-design of a future MGRS, as their preferences were not known. The objective of this article is to report as a case study the process of involving study participants and how this impacted the co-design of a proposed multi-generational research study, using a novel standardised reporting tool. METHODS: We used participatory action research to involve elderly research participants in the co-design of a proposed multi-generational cohort study between 2017 and 2019 using newsletters, telephone interviews and an in-person workshop. We used the novel ‘Standardised Data on Initiatives Alpha Version 0.1’ (STARDIT 0.1) to plan and report how participant involvement activities positively impacted the study design. RESULTS: Fifty-nine ASPREE-XT participants were interviewed by telephone and 18 participants attended a face-to-face event. Involving participants positively impacted the proposed study design by improving the research objectives, developing protocols, influencing funding decisions and improving ethics applications. Learning points included the importance of maintaining the ideals of ASPREE-XT (respect, quality and transparency); research participants’ preference for the option of receiving results (including genetic results); participants’ need for involvement in decisions about recruitment, data access, governance and other ethical issues; and the preference for different communication methods, including both face-to-face and online methods. Data from the process indicated it was highly valued by all stakeholders, including research participants, study staff and lead investigators. Involvement of participants was described by a lead study investigator of ASPREE-XT as “enormously helpful”. CONCLUSIONS: This case study demonstrates that including participants in the design of a research study positively impacted the study design, participants and researchers. Using a standardised reporting tool to describe the methods and impacts provides a way for learning from this case study to inform future research studies planning to involve people. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40900-021-00271-4.